Community Perception of The Conversion of Forest Land Into Building Land in Bangsar South Malaysia - Annisa, Revi; Akhubar Ali, Abishaah BT (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The conversion of land function in Bangsar South Malaysia occurred due to the development of forest land use into building land. The conversion of this land has not been fully carried out and is still under construction. Some Malaysians reject the land conversion function by making a petition to refuse land conversion activities to be carried out in Bangsar South Malaysia. The purpose of this study was to find out the perception of Malaysian people about the conversion of forest land into building land in Bangsar South Malaysia. The collection data method used in this research is the interview technique. The results of this study indicate that the Malaysian public's perception of the conversion of forest land to building land in Bangsar South Malaysia showed disagreement with some of the reasons they put forward. The reasons for the refusal by the Malaysians include damaging to the forest areas, reducing buffer zones, causing the possibility of flooding, increasing environmental temperature, causing a lack of absorption of groundwater and reducing fauna habitat in the forest which causes the fauna to move towards residential areas and disturb the security of the surrounding population.